Enrichment Media Selection and Co-Culture Potential among Exoelectrogen Bacteria Vary with Ecological Factors - Khoirunnisa, Nur Syafira; Anwar, Syaiful; Sudadi, Untung; Santosa, Dwi Andreas (UI Scholars Hub, 2023)
Staphylococcus saprophyticus ICBB 9554 and Citrobacter freundii ICBB 9763 are exoelectrogen bacteria applied as microbial fuel cells (MFC). We selected enrichment media for both these exoelectrogen bacteria, characterized their synergistic traits, and evaluated the growth conditions under different ecological factors. In this study, different enrichment media, such as those containing sugar, molasses, and palm sugar (2, 4, and 6% w/v) were tested for S. saprophyticus ICBB 9554. Meanwhile, technical sodium acetate (NaAc), commercial vinegar 25%, and cider vinegar (5, 10, and 15 mM acetate concentration) were tested for C. freundii ICBB 9763. Both the exoelectrogen bacteria were tested for the synergistic trait by inhibitory test, metabolic activity, and electricity generation performance in MFC. Different ecological factors, including salinity (2, 3, and 4 dS/m), culture media pH (5.8, 6.5, and 6.9), and temperature (20 °C, 27 °C, and 31 °C) were investigated for bacterial growth. The selective enrichment medium ingredient for S. saprophyticus ICBB 9554 was 2% molasses while that for C. freundii ICBB 9763 was 0.05 M technical sodium acetate. Both bacteria were suspected to grow synergistically and could be inoculated simultaneously as a co-culture in MFC. The effect of different ecological factors indicated that co-culture could grow better than pure culture. This study's findings provide important data on potential enrichment media for exoelectrogen bacteria that are beneficial for scale-up to reduce the operational cost.